Using of Social Media in School Management: Experience of Ukraine and United States of America (Educational Dimension, 2020)
The article presents the results of the analysis of using of social media in school management in Ukraine and United States of America. Social media is broadly defined as a lot of relatively inexpensive and widely available electronic instruments that allow any person to publish and receive information, collaborate and build relationships with other people. The authors of the article break up social media into social networks, blogs, content hosting. There are some constructive conclusions made in the article. The educational opportunities of social media among Ukrainian specialists are very underestimated. The value of social media as an instrument of the educational process is undeservedly belittled. Many educators treat them with neglect and skepticism, considering social media exclusively as an entertaining resource. Using of social media for educational purposes is perceived by American students, teachers, researchers as self-evident and inalienable function. The American didactic experience reveals that social media can be successfully used to arrange the work of the teaching staff and students, hold individual and collective consultations enhancing intellectual and creative potential of students.